Microgravity Monitoring Technology for Deep Gas-Reservoir Development based on Dixi 121 Wellblock in Xinjiang Oilfield - Zongfang HU; Qingxiong HU; Yun CAI; Changrui ZHANG; Quandang SHI; Guihong XU; Jianqiang QIN; Yuangang XIE; Shenshen DENG; Hewen ZHU; Xue BAI (CT Lilun yu yingyong yanjiu)
The difference in natural-gas enrichment significantly affects the underground medium density and thus the surface gravity. Microgravity monitoring technology monitors the morphological changes of a gas-reservoir development zone by measuring the surface gravity to obtain the change information of gas-reservoir development. The separation and extraction of gravity anomalies in microgravity monitoring is necessitated to accurately characterize the changes in gas-reservoir development intervals. The depth recursive method is the preferred method for separating residual gravity anomalies of different scales and extract reliable residual gravity anomalies. Considering the Dixi 121 well area of Xinjiang oilfield as an example and using the dynamic data of oil and gas drilling and production, the relationship between residual microgravity anomalies and reservoir characteristics is investigated in this study. The application of microgravity technology to the development of gas reservoirs in the middle and deep reservoirs is achieved, and a sand-ground ratio forward model is innovatively established for the geological conditions of the study area to analyse the response of the sand thickness in the residual gravity anomaly field. The findings of the study indicate that microgravity technology is an efficient method for developing reservoirs of middle and deep reservoirs. the higher the sand-ground ratio of the reservoir section, the lower the residual microgravity anomaly, which is in accordance with forward modelling and the distribution law of the sand-body depicted by seismic data.